2015
DOI: 10.3109/15376516.2014.1003359
|View full text |Cite
|
Sign up to set email alerts
|

Rutin potentially attenuates fluoride-induced oxidative stress-mediated cardiotoxicity, blood toxicity and dyslipidemia in rats

Abstract: This study was undertaken to evaluate cardio protective effect of rutin against sodium fluoride (NaF)-induced oxidative stress-mediated cardiotoxicity and blood toxicity. Cardiac injury was induced by daily administration of NaF 600 ppm in distilled water for four weeks. The animals exposed to NaF exhibited a significant increase in levels of cardiac serum markers, lipid peroxidative markers, serum total cholesterol, LDL, triglycerides and decrease in HDL levels. Decrease in hematological parameters, namely he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 33 publications
3
30
0
Order By: Relevance
“…The inhibition of lipid peroxidation was also determined by the quantification of the levels of MDA, which is a marker of oxidative damage to the lipids found in the erythrocyte membranes [49]. Umarani et al [50] reported that the flavonoid rutin, also present in the EEHS, promoted the inhibition of lipid peroxidation in the heart tissue of rats subjected to oxidative stress. Henneberg et al [51] reported the ability of rutin to sequester reactive oxygen species in human erythrocytes subjected to oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of lipid peroxidation was also determined by the quantification of the levels of MDA, which is a marker of oxidative damage to the lipids found in the erythrocyte membranes [49]. Umarani et al [50] reported that the flavonoid rutin, also present in the EEHS, promoted the inhibition of lipid peroxidation in the heart tissue of rats subjected to oxidative stress. Henneberg et al [51] reported the ability of rutin to sequester reactive oxygen species in human erythrocytes subjected to oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…Only rutin possessed the ability to attenuate cardiac I/R-associated hemodynamic alterations [159]. In addition, rutin increased anti-oxidant molecules and reduced cells necrosis and apoptosis and overall cardiac dysfunction in rats exposed to sodium fluoride-induced oxidative stress [160]. …”
Section: In Vivo Effects Of Polyphenols Against Oxidative Stress-imentioning
confidence: 99%
“…They are equipped with an effective and complex antioxidant system against oxidative stress, including protective enzymes and biological antioxidants such as superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase, reduced glutathione (GSH), and metallothionein (MT) . However, these endogenous antioxidants system can become overwhelmed as a result of over generation of reactive oxygen species (ROS), thereby triggering oxidative cells damage, inflammation, and endothelia dysfunctions which make these organs susceptible to injury . Heart has been reported to be the main target of mitochondrial injury owing to the inhibition of antioxidant defenses and activation of pro‐inflammatory cytokines .…”
Section: Introductionmentioning
confidence: 99%
“…11 Heart has been reported to be the main target of mitochondrial injury owing to the inhibition of antioxidant defenses and activation of pro-inflammatory cytokines. 11 Hence cardiac cells are easily susceptible to reactive oxygen species, which is the determinant of oxidative tissue damage.…”
Section: Introductionmentioning
confidence: 99%